Proceedings of First Conference for Engineering Sciences and Technology: Vol. 2 2018
DOI: 10.21467/proceedings.4.20
|View full text |Cite
|
Sign up to set email alerts
|

High Density Polyethylene/Libyan Kaolin Clay Nanocomposites: Effect of Clay Particle Size on Rheological, Surface and Mechanical Properties

Abstract: This research work focuses on the effect of Libyan Kaolin clay particle size on the reheological, surface and mechanical properties of high density polyethylene (HDPE)/clay nanocomposites. Three polymer clay nanocomposites (PCNs) using 2 wt.% clay with different particle size (< 75, 75-150 and 150-300 μm) and 2 wt.% polyethylene grafted maleic anhydride (PE-g-MA) were prepared by melt processing method. The rheological (viscosity and melt flow rate), surface (wettability/hydrophilicity), and mechanical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Our results showed that 2wt% kaolin clay added to HDPE enhanced its impact resistance up to 33% compared to virgin HDPE. Another study [27] showed the particle size of kaolin clay has a significant effect on the mechanical properties of HDPE composites. Clay particles sizes of 75-150 µm appear to have better overall properties compared to composites containing clay particles with sizes of <75 and > 150 µm.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that 2wt% kaolin clay added to HDPE enhanced its impact resistance up to 33% compared to virgin HDPE. Another study [27] showed the particle size of kaolin clay has a significant effect on the mechanical properties of HDPE composites. Clay particles sizes of 75-150 µm appear to have better overall properties compared to composites containing clay particles with sizes of <75 and > 150 µm.…”
Section: Introductionmentioning
confidence: 99%
“…However, broader applications of these materials are limited by technological challenges related to low-cost improvement prospects [ 5 ]. Polymer clay nanocomposites (PNCs), which are among the most promising materials for a number of applications, have attracted the attention of scientists in recent years due to their superior thermal, mechanical, magnetic, optical, dielectric or electromagnetic and barrier properties compared to virgin polymers and traditional microcomposites [ 6 , 7 , 8 , 9 , 10 ]. Today, polymer clay nanocomposites are considered priority systems because clay has a high aspect ratio and a flat morphology [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer nanocomposites (PNCs) have shown an overwhelming rise in their usage in various military and defense sectors such as military medicine, sensing, smart structures and textiles, military weapons, power generation and management and aerodynamics [ 4 ] The broader applications of these materials are limited due to the technological difficulties that are related to the low-cost improvement expectations [ 5 ]. Polymer/clay nanocomposites (PNCs) constitute a new class of composite materials that have been studied in recent years due to their superior thermal, mechanical and barrier properties compared to virgin polymer or traditional microcomposites [ 6 , 7 , 8 , 9 ]. Currently, the PNC material is considered to be an encouraging system since the clay has a high aspect ratio and a platy morphology [ 11 ].…”
Section: Introductionmentioning
confidence: 99%